THE INFLUENCE OF WORK ABILITY AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE GUNUNG SUGIH SUB-DISTRICT OF THE CENTRAL LAMPUNG DISTRICT - Samad, Abdul; Febriansyah, Febriansyah (University of Sang Bumi Ruwa Jurai, 2023)
The effectiveness of operations and the success of achieving the goals of an organization is determined by how much motivation is given by members to optimize their performance. Therefore, the element of human resources (HR) needs special attention, handling and treatment in addition to other factors because of its departure as the subject of implementing the policies and operational activities of an organization in line with the objectives of the organization itself. An additional effort is to increase the availability of facilities that are expected to help employees carry out their duties and functions efficiently and effectively. Among the problems faced by employees in Gunung Sugih Sub-district, Central Lampung Regency are as follows: less than optimal work ability, such as employees' lack of understanding of the latest technology and science, which is considered as one of the factors that hinder their performance; less motivation, which is shown by employees only waiting for orders from superiors and being less productive; and poor work performance. This research uses descriptive quantitative research methods, namely research methods that use data in the form of numbers in analyzing the facts found which aim to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This study used 40 respondents. The purpose of this study was to determine. The effect of Work Ability on employee performance, the effect of Work Motivation on employee performance, the effect of Work Ability and Work Motivation together on employee performance there is an effect of Work Ability (X1) on Employee Performance (Y) of 71.1%. There is an effect of Work Motivation on Employee Performance of 79.3%, there is an effect of Work Ability and Work Motivation together on Employee Performance of 80.8%.